Effects of diet processing method on growth performance of segregated early-weaned pigs - Sawyer, J.T.; Woodworth, J.C.; O'Quinn, P.R.; Nelssen, Jim L.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A 28-d growth trial was conducted to evaluate the effects ofdifferent diet processing methods on growth perfornlance of segregated early-weaned pigs. From d 0 to 14, pigs were fed diets processed by one of four different methods: meal, universal pellet cooker CUPC), expanded, or pelleted. Pigs fed pelleted or UPC diets had improved ADO and F/G, and pigs fed meal diets had the poorest ADO and F/G. From d 14 to 28, pigs were fed one of six diets consisting of complex meal and expanded diets and two (least cost and complex) UPC and pelleted diets. From d 14 to 28, pigs fed the complex pelleted diet had numerically the highest ADG and best F/G compared to pigs in the other treatments; however, ADG and F/G were not significantly different from those of pigs fed the meal diet. Complex pelleted or UPC diets improved growth performance compared to least cost diets. Thermal processed, least-cost diets will not elicit similar or improved growth performance compared to complex diets. These data suggest that processing techniques influence growth performance more in the early nursery phases than in later phases, and that pigs fed UPC or pelleted diets have the best growth performance.
Keywords: Swine; Weanling pigs; Diet processing; Growth